Complete mitochondrial genome of the snakehead (Channa gachua) and its phylogeny. Issue 2 (3rd July 2019) - He, Bin; Liu, Xingguo; Huan, Yingying; Che, Xuan; Yan, Tao; Yan, Jungang; Long, Zhihai; Li, Bin; Wen, Zheng-Yong
Abstract: In present study, the mitochondrial genome (mitogenome) of Channa gachua was determined and the phylogenetic relationship of Channidae fish was reconsidered. The mitogenome of the C. gachua is 16547 bp in length, containing 13 protein coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosome RNA genes (rRNAs), a control region (D-loop) and an origin region of replication on the light-strand (OL ). The overall nucleotide composition is 28.32% A, 26.58% T, 29.41% C, 15.69% G, with 54.90% AT, respectively. Phylogenetic analyses revealed that C. gachua belongs to the genus Channa and shares a close relationship with C. marulius and C. striata .